Penerapan Metode Pembelajaran SQ3R Berbantuan Internet Terhadap Hasil Belajar Siswa Kelas X Pada Materi Sistem Periodik Unsur Di SMA Labschool Palu - Alep, Boni; Walanda, Daud K.; Hamzah, Baharuddin (Universitas Tadulako, 2015)
Internet is a global network connecting thousands and even millions of computer networks with a personal computer so that the user can obtain a variety of information from wider sources. This internet service is used to assist the implementation of the SQ3R learning method that is expected to enrich the literature. The SQ3R learning method is a method of learning which uses the reading technique intensively and rationally to understand the main ideas, the details of a reading, and a comprehensive understanding of a passage with the steps i.e. surveying, asking, reading, communicating, and reviewing. The aim of this study was to determine the effect of the implementation of SQ3R learning method internet-assisted to the learning outcomes (cognitive) of students in the class X on the material periodic table of elements at Senior High School Labschool Palu. This research was a quasi-experimental with non-randomized pre-test and post-test control groups design. This research was carried out by holding two groups of class X science 1 as the control group (n = 19) and Class X science 2 as the experimental group (n = 18).Testing of research data used t-test statistical analysis one side (right side) with the prerequisite tests: normality and homogeneity tests. The results of the data analysis obtained the average value (X1 ) of experiment class was 83.94 with a standard deviation of 8.24 and (X1 ) of control class was 77.78 with a standard deviation of 8.54. Results of the hypothesis testing using statistical t-test one side (right side) obtained tcount>ttable value was 1.867 > 1.690 with a confidence level (Î±) = 0.05 and a degree of freedom (df ) = 35. Based on the results of hypothesis testing, then Ho is rejected and H1 is accepted so it can be concluded that the SQ3R learning method internet-assisted on the material Periodic System of Elements has a positive influence on the learning outcomes of students in the class X at Senior High School Labschool Palu.